Mobilizing Rural Institutions for Improving Governance and Development - Agrawal, Arun (World Bank, Washington, DC, 2012)
Local institutions play a fundamental role in governing access to resources, shaping delivery of services, and determining the experience of governance at local level. They are the principal mechanism to channel external interventions, resources, and assistance to poor households, women, and disadvantaged groups. This note presents the findings of a five-country research project, which focused on the role of local rural institutions and their institutional networks in shaping governance and livelihoods outcomes in rural areas, particularly for more marginal and disadvantaged populations. The first section outlines the Institutional Analysis and Development (IAD) framework that guided the case studies and analysis. The second summarizes key findings on how to promote better governance and livelihoods outcomes through local institutions. Two of the major findings of the study are that better performance on accountability is positively associated with greater equity in benefit distribution; and that stronger institutional linkages play a positive role in enhancing livelihoods, and in the distribution of livelihoods benefits. The third section presents implications of the study. The note is relevant to a large portfolio of World Bank development projects that partner with local institutions as entry points to achieve their objectives.